ҚОРАҚАЛПОҒИСТОН РЕСПУБЛИКАСИНИНГ ЖАНУБИЙ ҲУДУДИ MELIPOTINI ТРИБАСИ ТАНГАЧАҚАНОТЛИЛАРИНИНГ ТУР ТАРКИБИ ВА БИОЭКОЛОГИК ХУСУСЯТЛАРИ - Бекчанов, Х.Ў.; Ядгорова, Н. (SCIENCE and SOCIETY, 2024)
In this article the species composition of the Melipoti tribe of the desert region of the Yuge Republic of Karakalpakstan and the simultaneous analysis of the bioecological characteristics and geographical distribution of the species are presented in this state.
Keywords: zoogeography; synanthropic and subsynanthropic; submicrothermal; forest; anthropogenic